Low-Cost Intelligent Robot Car with Autonomous and Manual Wireless Navigation Systems (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This research paper introduces an abstract avoidance system controlled via Bluetooth and voice commands using an Arduino board. Ultrasonic sensors detect obstacles, providing real-time data for the system. Users can remotely control the system's movements and navigate through complex environments using a mobile device connected via Bluetooth. Additionally, voice commands enhance usability and convenience. The integration of hardware components, including ultrasonic sensors, an Arduino board, and a Bluetooth module, along with algorithm development for obstacle detection and communication protocols, enables the system's functionality. This versatile system finds applications in robotics, automation, and smart environments where obstacle avoidance is crucial. By combining Bluetooth and voice control, this project offers an efficient and user-friendly solution for enhancing control and safety in various real-world scenarios.